The Effect of The Hakkarainen Model on The Achievement And Development of Logical Thinking In The Teaching Methods Course For Students At The Institute of Fine Arts. (Journal of the College of Basic Education, 2025)
the current research aims to identify the effect of the Hakkarainen model on the academic achievement and development of logical thinking among female students at the lnstitute of Fine Arts in the subject of Teaching Methods of Art Education .To achieve this goal , the researcher adopted an experimental design with two equivalent groups (experimental and control ,with pre-testing for equivalence and post-testing ) . the research population consisted of all third-year female students in the morning study program at the Fine Arts lnstitutes for Girls the Baghdad Education Directorates (Al-Rusafa and Al-Karkh ) for the academic year (2024 / 2025) .A purposive sample was selected from third-year students at the Fine Arts lnstitute for Girls (Morning Study Program) under the Baghdad Al-Karkh / 2 Education Directorate , totaling 59 students distributed across three departments . The department representing the experimental sample was chosen randomly (by lottery) , comprising 20 students , who were equally divided into two classrooms . The two groups were matched in variables such as chronological age ( calculated in months ) , intelligence , pre-test academic achievement , and pre-test logical thinking scores . The researcher prepared two to tools : A 25-item multiple-choice academic achievement test for Teaching Methods of Art Education and a logical thinking skills scale based on the classification by Obidat and Suhaila (2005) for primary and secondary logical thinking skills( scale domains ) . After collecting and statistically analyzing the data , the results showed that the experimental group outperformed the control group in both the academic achievement test for Teaching Methods of Art Education and the logical thinking scale . Based on the findings , the researcher presented several recommendations and suggestions .